Pillared-bilayer zinc(ii)–organic laminae: pore modification and selective gas adsorption1. Issue 33 (7th September 2015) - Lee, Li-Wei; Luo, Tzuoo-Tsair; Lo, Sheng-Han; Lee, Gene-Hsiang; Peng, Shie-Ming; Liu, Yen-Hsiang; Lee, Sheng-Long; Lu, Kuang-Lieh
<x xml:space="preserve">Abstract</x> Three Zn(ii)-based pillared-bilayer MOFs were systematically synthesized. Their unusual structural characteristics allow these pillared-bilayer MOFs to serve as excellent models for studies of gas adsorption properties.